Synthesis of Ternary Homogeneous Azeotropic Distillation Sequences: 2. Flowsheet Identification - Sutijan, Sutijan; Jobson, Megan; Smith, Robin (ASEAN Journal of Chemical Engineering, 2013)
This paper presents a systematic methodology for flowsheet generation for separating binary azeotropic mixtures using homogeneous azeotropic distillation. A new classification system for ternary mixtures using ‘standard distillation line maps’ defined in Sutijan et al. (2012) is employed. The new characterisation system is able to link candidate entrainers to flowsheet structures which can facilitate the separation. The sequences considered include pressure-swing distillation, two and three-column flowsheets with or without boundary crossing and the use of single and double-feed columns. For a given ternary mixture, suitable flowsheet structures that can facilitate the separation can be automatically identified. The method is illustrated using examples.